(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the intricate difference between Phrasal verbs and phrasal nouns, and concept of both of them, their importance in English grammar. Many people know how to use them in grammar, but they aren’t aware of difference of them. Phrasal noun and phrasal verb make our speech more expressive and efficient. They are common in daily talk. Instead of a long sentence, we use them to express ideas clearly and fast.